Effect of different surface treatments on retention and fracture strength of zirconia crowns over Ti-base zirconia abutments - Mehran Falahchai; Hamid Neshandar Asli; Mehdi Daneshvar; Amirreza Hendi (Heliyon, 2024)
Background: Limited evidence suggested different outcomes of surface treatment methods on zirconia abutments and crowns. Therefore, we investigated the effect of grooving, hot etching, and airborne particle abrasion (APA) methods on zirconia crowns over Ti-base zirconia abutments retention and fracture strength. Materials and methods: In this in vitro study, 110 zirconia crowns and abutments were divided into five groups, including APA for crown and grooved zirconia abutment (APACr-GrAb), APA for crown and hot etching zirconia abutment (APACr-HtAb), grooved modified zirconia crown and APA for zirconia abutments (GrCr-APAAb), hot etching modified zirconia crown and APA for zirconia abutments (HtCr-APAAb), and APA for both crown and zirconia abutments (control group). The retention and fracture strength were measured. Data were analyzed by ANOVA, Tukey, Kruskal-Wallis, and Mann-Whitney with Bonferroni correction tests (α = 0.05). Results: Hot etching and grooving on the crown or abutment significantly resulted in higher retention (P < 0.001). The fracture strength significantly differed among the five groups (P = 0.041), with the highest fracture strength observed in the GrCr-APAAb group and the lowest for the APACr-GrAb group; however, no significant differences were found in pairwise comparisons between groups (P > 0.05). By considering both fracture strength and retention, grooving, hot etching, and APA were confirmed for better crown and abutment function, respectively. Conclusion: Grooving surface treatment was the best method due to its high fracture strength and retention, followed by hot etching due to its high retention compared to APA, which can be considered a suitable method for cementing zirconia crown on zirconia abutments.